PENGARUH WELLNES TOURISM EXPERIENCE TERHADAP TOURISM ENGAGEMENT MELALUI VARIABEL TOURISM INSPIRATION - Putra, Gilang Kharisma (Fakultas Ekonomi, Universitas Semarang, 2024)
The aim of this research is to test whether wellness tourist expertise can create tourist engagement behavior. We also tried to add the tourist inspiration variable as a mediating variable.This research uses a quantitative research methodapproach. Using a purposive sampling method in the sampling technique, where the samples taken will later be filtered based on certain criteria. The sample criteria in this research are visitors to the Medini Kendal Regency tourist attraction who have visited more than 3 times. Based on these criteria, a sampling of 77 visitors was selected. This research uses primary data, where this data was obtained directly. Based on the table of hypothesis test processing results above, the relationship between the tourist wellness experience variable and tourist engagement is with a t statistic of 2.255 and a p value of 0.024. These results show that the wellness tourist experience variable has a positive and significant influence, the relationship between the tourist inspiration variable and tourist engagement with a t statistic of 6.717 and a p value of 0.000. These results show that the tourist inspiration variable has a positive and significant influence on tourist engagement. The relationship between the wellness tourist experience variable and tourist inspiration with a t statistic of 17.256 and a p value of 0.000. These results show that the wellness tourist experience variable has a positive and significant influence on tourist inspiration. The role of the tourist inspiration variable in mediating the relationship between the wellness tourist experience variable and tourist engagement with a t statistic of 5.965 and a p value of 0.000. These results show that tourist inspiration is able to mediate the relationship between the tourist wellness variable and the tourist engagement variable